If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2mn + 9mp = 0 Solving 2mn + 9mp = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'm'. m(2n + 9p) = 0Subproblem 1
Set the factor 'm' equal to zero and attempt to solve: Simplifying m = 0 Solving m = 0 Move all terms containing m to the left, all other terms to the right. Simplifying m = 0Subproblem 2
Set the factor '(2n + 9p)' equal to zero and attempt to solve: Simplifying 2n + 9p = 0 Solving 2n + 9p = 0 Move all terms containing m to the left, all other terms to the right. Add '-2n' to each side of the equation. 2n + -2n + 9p = 0 + -2n Combine like terms: 2n + -2n = 0 0 + 9p = 0 + -2n 9p = 0 + -2n Remove the zero: 9p = -2n Add '-9p' to each side of the equation. 9p + -9p = -2n + -9p Combine like terms: 9p + -9p = 0 0 = -2n + -9p Simplifying 0 = -2n + -9p The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
m = {0}
| 4(x+3)-7x=6 | | 10-3x+8=30+2x+48 | | 17x+8=42 | | 9x-6-5x=8+x-14 | | 56-6x=3x+21 | | 5-7x=3x+21 | | -70-9x=43-21x | | (5y-2)=52 | | 14-8x+6-5x=10+2x-5 | | 6x+18=116-6x | | (x+2)(2-x)=6x-x | | 2x+36=21x-36 | | 17-6x=4x-8 | | 9-5k+2k=k-23 | | x^2+4x-1=9x-5 | | 6x+30=13-33 | | x^2+8x-2=7 | | x^2-(a+2b)x+b^2+ab=0 | | 24a=36 | | 12-x=30-4x | | 3x+4=5x-16 | | x^2+32x-196=0 | | x-17=6x+8 | | 9x-5=x+19 | | 9x+6=6x+10 | | 7x-20=04-3x | | 7(2x-5)=42 | | 21-7x=10+4x | | x+2=-3x+30 | | (5x-3)*2+(2x+1)*2=34 | | .4x=-5.3 | | 2x+12=4x+2 |